Ganglioside shedding and changes in ceramide biosynthesis in human ovarian tumors - Dyatlovitskaya, E V; Andreasyan, G O; Malykh YaN; Rylova, S N; Somova, O G (Biochemistry (Moscow), 1997)
The contents and composition of ceramides and gangliosides were measured in human ovarian tumors (benign and malignant) and sera of tumor patients. In tumors (especially malignant) the content of ceramides is decreased compared to that in normal tissue, and the malignant tumor ceramides contain significant amounts of sphinganine which is absent in the ceramides of normal tissue, suggesting an alteration in ceramide biosynthesis. The content of gangliosides in tumors is also decreased. The major gangliosides of normal and tumor ovarian tissues are GM3 (sialocsyllactosyl ceramide) and GD3 (disialosyllactosyl ceramide). In tumors, the GD3 content is significantly decreased. The ceramide/ganglioside molar ratio in tumors is shifted toward gangliosides. In sera of tumor patients, ceramide content does not change, ganglioside content (especially that of GD3) increases compared to that in sera of healthy subjects due to ganglioside shedding from the surface of tumor cells, and the ceramide/ganglioside molar ratio decreases. These changes may stimulate tumor growth because of the opposite effects of ceramides and gangliosides: ceramides suppress tumor growth and gangliosides suppress antitumor activity.